2007
DOI: 10.1016/s1472-6483(10)60782-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between two forms of vaginally administered progesterone for luteal phase support in assisted reproduction cycles

Abstract: The use of progesterone for luteal phase support has been demonstrated to be beneficial in assisted reproduction cycles using gonadotrophin-releasing hormone analogues (GnRHa). Two micronized progesterone preparations are available for vaginal administration: capsules and gel. The objective of this study was to compare the efficacy of these two forms for luteal phase support in assisted reproduction cycles. A total of 244 couples undergoing IVF/intracytoplasmic sperm injection cycles were included in the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 17 publications
0
35
0
1
Order By: Relevance
“…On the third day following oocyte retrieval, embryo quality was evaluated and embryo transfer was performed (the fresh group) or the entire cohort was cryopreserved (the freeze-all group). Patients submitted to a fresh embryo transfer received vaginal micronized progesterone in gel formulation (Crinone® 8%; Merck Serono) for a single daily administration [25] starting on the day of oocyte retrieval. Progesterone was used for at least 13 days, when a pregnancy test was performed, and until 9 weeks if pregnancy was confirmed.…”
Section: Patient Selectionmentioning
confidence: 99%
“…On the third day following oocyte retrieval, embryo quality was evaluated and embryo transfer was performed (the fresh group) or the entire cohort was cryopreserved (the freeze-all group). Patients submitted to a fresh embryo transfer received vaginal micronized progesterone in gel formulation (Crinone® 8%; Merck Serono) for a single daily administration [25] starting on the day of oocyte retrieval. Progesterone was used for at least 13 days, when a pregnancy test was performed, and until 9 weeks if pregnancy was confirmed.…”
Section: Patient Selectionmentioning
confidence: 99%
“…It suggested that initiating LPS treatment on either hCG day, oocyte retrieval day or embryo transfer day makes no difference as far as the ongoing pregnancy rates are concerned (respectively 20.8%, 22.7% and 23.6%) [7]. The general global approach to LPS in IVF treatments has been to use vaginal progesterone, particularly vaginal gel, due to its minimal side-effect spectrum and ease of application [24][25][26][27][28]. However, studies comparing different vaginal progesterone formulations with regard to IVF success did not go beyond a limited number [24][25][26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…The general global approach to LPS in IVF treatments has been to use vaginal progesterone, particularly vaginal gel, due to its minimal side-effect spectrum and ease of application [24][25][26][27][28]. However, studies comparing different vaginal progesterone formulations with regard to IVF success did not go beyond a limited number [24][25][26][27][28][29][30]. Detailed analysis of the available literature revealed a very limited number of studies investigating the differences of the vaginal forms, except for two recent large randomized trials [28,30].…”
Section: Discussionmentioning
confidence: 99%
“…The reminders were vitrified as previously published [16]. Luteal phase support was performed with a single daily administration of vaginal micronized progesterone in gel (Crinone 8 %, Merck Serono, Brazil), starting on the evening of day 1 after oocyte retrieval [17].…”
Section: Case Reportmentioning
confidence: 99%